Two new Incisitermes (Isoptera: Kalotermitidae) species from the Caribbean Basin, genetic relationships with other regional Incisitermes, and synonymy of Incisitermes tabogae with I. schwarzi - Scheffrahn, Rudolf H.; Austin, James W.; Szalanski, Allen L. (Zootaxa, 2024)
Two new species of Incisitermes are described from the soldier and imago caste: Incisitermes lisae sp. nov. (Yucatan Region) and Incisitermes mariae sp. nov. (Venezuela and Trinidad and Tobago). Incisitermes tabogae (Snyder, 1924) is reduced to a junior synonymy of Incisitermes schwarzi (Banks, 1920), known from Florida, the West Indies, and the Caribbean basin mainland. The phylogenetic relationships of these three species are compared with other Incisitermes of the region.